CD200R Combined Neutrophil-Lymphocyte Ratio Predict 90-Day Mortality in HBV-Related Acute-On-Chronic Liver Failure - Li, Yuxin; Kong, Yaxian; Shi, Ke; Huang, Yunyi; Zhang, Qun; Zhu, Bingbing; Zeng, Hui; Wang, Xianbo (Frontiers in Medicine, 2021)
Background: Survival of acute-on-chronic liver failure (ACLF) cannot be properly predicted based on clinical characteristics. Aims: This study aimed to develop a predictive model to evaluating the prognosis for hepatitis B virus-related ACLF (HBV-ACLF) based on specific laboratory and immune indicators. Methods: Baseline laboratory results were obtained and immune indicators were detected by flow cytometry. A predictive model, which estimates the prognosis at 90-day follow-up, was developed using data from a prospective study on 45 patients hospitalized of HBV-ACLF from June 2016 to April 2018 at the Beijing Ditan Hospital, Capital Medical University. The prognostic values of the predictive factors were determined by the area under the receiver operating characteristic (AUROC) curves. Results: Six factors exhibited statistical differences between the survival and non-survival groups: proportions of CD4+TN, CD4+TEM, CD8+TN, CD8+TEM, CD200R+CD4+T cells and neutrophil-lymphocyte ratio (NLR). CD200R combined with the NLR had an AUROC of 0.916, which was significantly higher than the AUROC values of CD200R+CD4+T cells (0.868) , NLR (0.761), model for end-stage liver disease (MELD) (0.840), MELD-Na (0.870), Child-Turcotte-Pugh (CTP) (0.580), or chronic liver failure-consortium ACLF (CLIF-C ACLF) score(0.840). At the cut-off point of -3.87, matching the maximum Youden index determined by ROC analysis, the positive predictive and negative predictive values for the mortality were 0.86 and 0.97, respectively. Conclusions: The 90-day prediction model based on baseline levels of CD200R+CD4+T cells and NLR offers potential predictive value for the mortality of HBV-ACLF.